SCHOOL PRINCIPAL LEADERSHIP MANAGEMENT IN IMPROVING TEACHER PERFORMANCE AT SDN SERANG 03 - Een Suhaeni; Andriani Sariwardani (Cakrawala Pedagogik, 2025)
This qualitative study at Serang 03 Public Elementary School investigates the principal's management strategies for improving teacher performance. The research aims to evaluate the current level of teacher performance and identify the principal's management approaches to enhance it, ultimately understanding their role in creating a supportive and motivating work environment. Data was collected through observation, interviews, and document analysis, and analyzed via data reduction, presentation, and conclusion. The findings reveal that the principal employs standard management functions—planning, organizing, implementing, and supervising—to improve teacher performance, which is assessed through indicators like mastery of materials, classroom management, resource utilization, administrative skills, assessment accuracy, and teaching interaction quality. The principal's planning management is effective in improving teacher performance through systematic efforts to enhance discipline, encourage participation, and provide professional development via seminars, Teacher Working Groups, and Independent Learning curriculum training. Organizational management, characterized by clear rules and assignments, also effectively boosts teacher performance. Implementation management is satisfactory, particularly in enforcing discipline and conducting the teaching-learning process. Finally, comprehensive supervision management proves effective in improving teacher performance through thorough monitoring and evaluation of all school programs.